Evaluating fiscal policy reforms using the fiscal frontier - Xiaoshan Chen; Campbell B. Leith; Mattia Ricci (European Commission, Joint Research Centre (JRC), 2023)
We develop a Fiscal Frontier which traces out the maximum government debt level that can be sustained at a given welfare cost. Through duality, the intertemporal policy mix underpinning the Frontier mirrors standard Ramsey policy and defines an upper limit on the welfare gains that can be achieved by any fiscal reform. The Frontier is then used to evaluate a variety of fiscal reforms: (1) one-off changes in tax instruments considered in Laffer curve calculations, (2) a gradual reduction in capital taxation proposed by Lucas (1990), and (3) fiscal consolidation strategies akin to those considered by the Congressional Budget Office. Conventional Laffer curve calculations significantly under-estimate the sustainable debt of the US. The desirable pace of capital tax abolition has slowed since the 1970s, but the reform remains close to the Frontier. Achieving debt reduction targets considered by the Congressional Budget Office is typically very costly, especially when the fiscal consolidation is large and must be achieved quickly, but a simultaneous capital tax reform can more than offset those costs in all cases we consider.
Keywords: E62; H30; H60; 330; Laffer Curve; Optimal Policy; Debt Sustainability; FiscalLimit; Duality